Pengaruh Kepercayaan Merek, Kualitas Produk dan Harga Terhadap Keputusan Pembelian Produk Emina - Hesti Rahmah Maulidah; Ana Noor Andriana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to determine whether brand trust, product quality and price affect both partially and simultaneously on purchasing decisions on Emina cosmetic products. The location of the study in Samarinda City with the population in this study is adolescent consumers who use or have purchased Emina products. The sampling technique uses non-probability sampling with the Purposive sampling method and the sample obtained is as many as 100 respondents. The primary data in this study is the result of filling out a questionnaire distributed using google form and secondary data in this study was obtained from previous research journals and reference books related to research. The data analysis technique used is multiple linear regression analysis using the help of SPSS software version 25. The results showed that partially the brand trust variable had a significant effect on the purchase decision, the product quality variable had a significant effect on the purchase decision, and the price variable had a significant effect on the purchase decision. The simultaneous results of brand trust variables and product quality and price have a significant effect on the purchase decision of Emina products in adolescents in Samarinda City. The results of the coefficient of determination test got a value of 0.460 which means that the level of relationship between brand trust, product quality and price variables to purchasing decision variables in Emina products is 46.0% while the remaining 54.0% is influenced by other variables that are not included in this study.